A brief history of bacterial growth physiology - Schaechter, Moselio (Frontiers in Microbiology, 2015)
Arguably, microbial physiology started when Leeuwenhoek became fascinated by observing a Vorticella beating its cilia, my point being that almost any observation of microbes has a physiological component. With the advent of modern microbiology in the mid-19th century, the field became recognizably distinctive with such discoveries as anaerobiosis, fermentation as a biological phenomenon, and the nutritional requirements of microbes. Soon came the discoveries of Winogradsky and his followers of the chemical changes in the environment that result from microbial activities. Later, during the first half of the 20th century, microbial physiology became the basis for much of the elucidation of central metabolism. Bacterial physiology then became a handmaiden of molecular biology and was greatly influenced by the discovery of cellular regulatory mechanisms. Microbial growth, which had come of age with the early work of Hershey, Monod, and others, was later pursued by studies on a whole cell level by what became known as the “Copenhagen School.” During this time, the exploration of physiological activities became coupled to modern inquiries into the structure of the bacterial cell. Recent years have seen the development of a further phase in microbial physiology, one seeking a deeper quantitative understanding of phenomena on a whole cell level. This pursuit is exemplified by the emergence of systems biology, which is made possible by the development of technologies that permit the gathering of information in huge amounts. As has been true through history, the research into microbial physiology continues to be guided by the development of new methods of analysis. Some of these developments may well afford the possibility of making stunning breakthroughs.